1997
DOI: 10.1080/02841859709172393
|View full text |Cite
|
Sign up to set email alerts
|

MnDPDP for MR imaging of the liver

Abstract: Purpose:To evaluate the diagnostic efficacy and safety of MnDPDP (Teslascan) in enhanced MR imaging.Material and Methods: In 2 multiple independent trials in Europe 624 patients weregiven MnDPDP intravenously at 5 pmolkg b.w. Patients underwent an unenhanced MR examination comprising T1 -weighted spin-echo and breath-hold gradient-echo sequences and a T2-weighted spin-echo sequence. The T I sequences were repeated after the administration of MnDPDP. In a subgroup of 137 patients the results of the enhanced MR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This process can result in significant enhancement of fluorescence and simultaneously MR signals. This resultant MR signal enhancement is superior to those reported in many manganese-based contrast systems by release of free Mn 2+ ions. , To overcome reported adverse effects from over dosage or leakage of Mn (e.g., cardiotoxicity, nausea, headache, and pruritus), the incorporation of fullerenes could provide high-relaxivity MRI contrast at reduced dosage levels and significantly suppress the release of free Mn 2+ ions, and both approaches have resulted in reduced toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…This process can result in significant enhancement of fluorescence and simultaneously MR signals. This resultant MR signal enhancement is superior to those reported in many manganese-based contrast systems by release of free Mn 2+ ions. , To overcome reported adverse effects from over dosage or leakage of Mn (e.g., cardiotoxicity, nausea, headache, and pruritus), the incorporation of fullerenes could provide high-relaxivity MRI contrast at reduced dosage levels and significantly suppress the release of free Mn 2+ ions, and both approaches have resulted in reduced toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…30 In a European phase III clinical trial, adverse events, such as nausea, headache, and pruritus, were observed in 7% of the 624 patients. 478,479 Transient decreases in alkaline phosphatase levels and sensations of heat and flushing with high injection rates most likely related to peripheral vasodilatation have also been reported.…”
Section: Manganese-based Agentsmentioning
confidence: 99%
“…T 1 liver enhancement after intravenous infusion begins early, 1−2 min postinjection, maximizes within 5−10 min, and persists for several hours, allowing flexibility for patient scheduling when compared to Gd 3+ chelates. No longer on the market, for human clinical imaging to detect hepatic lesions, the approved dosage of Mn-DPDP was 5 μmol/kg, and approximately 15% was eliminated in the urine by 24 h postinjection and 59% in the feces by 5 days . In a European phase III clinical trial, adverse events, such as nausea, headache, and pruritus, were observed in 7% of the 624 patients. , Transient decreases in alkaline phosphatase levels and sensations of heat and flushing with high injection rates most likely related to peripheral vasodilatation have also been reported.…”
Section: Manganese-based Agentsmentioning
confidence: 99%